Lifetime Cancer Risk of Gamma Radioactivity Results from Smoking - Shousha, Hany A; Ahmad, Fawzia (Cancers Review, 2016)
Smoking is one of the causes of heart attack, lung cancer and cancers of mouth and larynx. The latter could be arises from exposure of those sensitive organs to a combination of both chemical carcinogenic and radiological exposure results from naturally occurring radionuclides in tobacco leaves. Coal is also used in smoking some types of tobacco products that could be carcinogenic due to presence of a high percentage of an organic matter with inorganic matter such as minerals and trace elements. Varieties of commonly available tobacco products as well as coal samples were examined for their radioactivity content using gamma ray spectroscopy and calculate associated radiological hazards. Results shows that the average concentrations of 226Ra, 232Th, and 40K in tobacco samples vary from 2.6±0.2 to 8.9±0.7 (average 5.4), 1.9±0.1 to 9.5±0.8 (average 4.5), and 517.4±15.5 to 2401.2±72 (average 1360.4) Bqkg-1. Measured activity concentration for coal samples ranged from 10.8±1.1 to 64.4±2.1 (average 40.2), 3.5±0.1 to 28.3±0.3 (average 15.7), and 49.2±0.4 to 301.2±9.5 (average 215) Bqkg-1 for 226Ra, 232Th, and 40K respectively. 137Cs activity concentrations in cigarettes and coal samples were ranged from 0.1±0.01 to 1.3±0.02 (average 0.5) and 2±0.01 to 5.8±0.8 (average 3.1) Bqkg-1 respectively. Radium equivalent, total annual effective dose and excess lifetime cancer risk were calculated. ELCR was higher than world’s average of 1.45x10-3 for tobacco and coal samples. In Egypt no special and clear regulations for monitoring radioactivity content in imported coal and tobacco leafs or its products, which appear to be necessary.